Prospects of development of small cities of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
The modern state and prospects of development of small cities of Kazakhstan, that are characterized the brightly expressed instability, violation of scientifically reasonable criteria of effective organization of municipal economy, unworked out of questions of adaptation to accordion globalization of economy, are examined in the article. The analysis of economy and social sphere of small cities allowed to distinguish inherent to them basic problems. To them behave: absence of effective strategies and programs of development of small cities, absence of facilities on development, dependence on higher budgets, low level and quality of life and high unemployment rate. In addition high economic dependence on images of the city enterprises, high percent of wear of objects of productive and transport infrastructure, and also ecological problems is saved in small cities. Basic directions of development of small cities it is been: perfection of structure of economy by diversification and creation of optimal combination of enterprises of different size and branch belonging, expansion of composition of functional specialization of cities, mastering of present near-by small cities raw mineral-material resources
Keywords: small cities; monofunctional structure of economy; city appearing enterprises; acuestss of population; Program of development of small cities